Factors affecting the communication experiences of newly diagnosed colorectal cancer patients. Issue 9 (September 2018) - Treiman, Katherine; McCormack, Lauren; Wagner, Laura; Roach, Nancy; Moultrie, Rebecca; Sanoff, Hannah; Bann, Carla; Street, Richard L.; Ashok, Mahima; Reeve, Bryce B.
Highlights: Patient-centered communication (PCC) is a key component of quality cancer care. We assessed PCC experiences among newly diagnosed colorectal cancer patients. Patients in poor physical health and mental health reported worse communication. The quality of communication varied across 6 domains of PCC and patient subgroups. PCC is a communication process over time, often with multiple providers. Abstract: Objective: This study assessed patient-centered communication (PCC) among newly diagnosed colorectal cancer patients. PCC, a key part of patient-centered care, contributes directly and indirectly to health-related quality of life, satisfaction with care, and other outcomes. Methods: We conducted a survey of patients in North Carolina, using a theoretically-based and validated measure that provides an overall PCC score and subscale scores for six PCC functions. Results: A total of 501 patients participated. The highest scores were for the PCC functions of Fostering Healing Relationships, Exchanging Information, and Making Decisions. The lowest scores were for the functions of Managing Uncertainty and Enabling Self-Management, yet these were functions respondents rated as most important. Respondents who thought about more than one health professional (versus oncologist) reported better communication. PCC also varied by treatment type, mental and physical health status, age, race, and education. Conclusion: Most patients reported good communication overall, however patients in poor physical health and mental health reported worse communication. The quality of communication varied across the PCC functions. Practice implications: Health professionals need to use a PCC approach that builds trust, respects the patient, provides salient information that patients can understand, provides emotional support, and facilitates the patient's engagement in care.